2019
DOI: 10.2106/jbjs.18.00631
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Injections Prior to Arthroscopic Rotator Cuff Repair Impacts the Risk of Surgical Site Infection

Abstract: Background: Corticosteroid injections are a common treatment for rotator cuff tears. Because of concerns of infection, a surgical procedure is often delayed following injections. The purpose of this investigation was to determine if there is a temporal relationship between corticosteroid injections and the risk of surgical site infection after arthroscopic rotator cuff repair. We hypothesized that the incidence of surgical site infection is higher in patients who received a preoperative injection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 21 publications
1
46
0
3
Order By: Relevance
“…18,19 However, the clinical relevance of wound healing after arthroscopic meniscectomy is likely limited because modern arthroscopic surgery is accomplished through small incisions. 17 Preoperative joint injections have been shown to increase the risk of postoperative infection after shoulder arthroscopy 13 and arthroplasty, 20 hip arthroscopy 21 and arthroplasty, [22][23][24] knee arthroplasty, 25 and elbow arthroscopy. 26 Previous investigations have found preoperative intra-articular injections within 3 months of hip arthroscopy (OR, 6.1) 21 and shoulder arthroscopy (OR, 1.6) 20 to be associated with an increased risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 However, the clinical relevance of wound healing after arthroscopic meniscectomy is likely limited because modern arthroscopic surgery is accomplished through small incisions. 17 Preoperative joint injections have been shown to increase the risk of postoperative infection after shoulder arthroscopy 13 and arthroplasty, 20 hip arthroscopy 21 and arthroplasty, [22][23][24] knee arthroplasty, 25 and elbow arthroscopy. 26 Previous investigations have found preoperative intra-articular injections within 3 months of hip arthroscopy (OR, 6.1) 21 and shoulder arthroscopy (OR, 1.6) 20 to be associated with an increased risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous investigations have found preoperative intra-articular injections within 3 months of hip arthroscopy (OR, 6.1) 21 and shoulder arthroscopy (OR, 1.6) 20 to be associated with an increased risk of postoperative infection. Forsythe et al 13 studied patients undergoing arthroscopic rotator cuff repair and found that intra-articular injections within 1 month of shoulder arthroscopy were associated with increased postoperative complications (OR, 1.7). Our investigation used similar methodology and found that a postoperative infection was 1.89 times more likely to develop in patients undergoing knee injection within 1 month of meniscectomy relative to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,49 Furthermore, we add to the literature another risk factor for detrimental postoperative outcomes in those undergoing RCR, which previously included patient age, 29 body mass index, 5 comorbidities, 46,53 open repair, 38 and preoperative and intraoperative steroid injections. 21,52 Moreover, opioid use is a risk factor that is both common and detrimental. Even small differences in the effect size are important in a procedure performed as commonly as arthroscopic RCR, with reports of up to 270,000 of these procedures being performed in the United States each year.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile,some researchers believe that timing and dose of injections prior to arthroscopic rotator cuff repair impacts the risk of infection [15]. Therefore, there is still great controversy regarding the safety and clinical e cacy of intra-articular corticosteroid injection after shoulder arthroscopy.…”
Section: Introductionmentioning
confidence: 99%